A Study of Music and Its Ability to Give Voice: A Photo-Elicitation Project Involving Youth In-Care and the Interpretation of Visuals - Anderson, Blake (My University, 2017)
In 2017 the Ontario government moved forward with new child welfare legislation, Bill 89, spelling out that the 47 Children’s Aid Societies in Ontario will be much more ‘child-centric’. I explore the historical context of the ‘child-centric’ language and commitments in the new Act, including tracing its origin by the Act’s incorporation of the Katelynn Principle and Article 12 of the 1989 United Nations Convention On The Rights Of The Child. How best to consult youth in-care is an essential, but a mostly unanswered question. Children Aid Societies across the province have a unique opportunity to implement alternative methods in engaging young people in consultation, should they pan out as viable and reliable strategies when consulting youth in-care. Tradition interview approaches are not always the best strategies when engaging youth. Visual research methods, such as photo-elicitation, have the potential of offering useful insights into children’s perspectives and experiences. The focus of my thesis is youth voice. I explore this topic through a study with young people in-care involved in a music group. I used focus groups and photo-elicitation as methods for data collection. An important question addressed by my thesis is whether a visual research method, such as photo-elicitation, helps in the consultation process with young people and whether some of the claims made about the approach are accurate when working with youth. Specifically, I explored claims made about photo-elicitation helping with increasing 'emotional type talk' and inquired into how the method may enhance the consultation process with young people. I consider these questions in the context of important epistemological and theoretical debates about arts-informed and visual research methodologies. Five youth who had involvement of being in-care and were a part of a music group at a local Children’s Aid Society participated in my study. My study found that the youth overall felt consulted and did feel a degree of influence in shared decision making with being in-care. My study also showed that although photo-elicitation did not generate more ‘emotional-type talk’, it does appear to enhance self-confidence, which seemed to support meaningful participation in the interview process. Although much more needs to be explored with the application of visual research methods, and social science researchers should be cautious in making exaggerated claims in support of the approaches, youth in-care can surely benefit from visual research methods such as photo-elicitation.
Keywords: child welfare; youth consultation; youth in-care; photo-elicitation; youth voice; music; postmodernism; visual research methods; youth participation